THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLES ON EMPLOYEE’S JOB SATISFACTION IN PT TRI AGUNG ABADI MEDAN - Susanto, Susanto (Media Bina Ilmiah, 2024)
The successful leader is if the leader is able to become the creator and driving force for subordinates to create an atmosphere and culture that can encourage the growth and development of employee performance. Leaders have the ability to provide a positive influence for employees to carry out work in accordance with the directed in order to achieve the goals set. With the style of leadership is expected to increase employee’s job satisfaction to improve the quality of work performance provided and ultimately improve the competitiveness of company in the tight competition. The purposes of this research are to know there is influence of transformational leadership style towards job satisfaction at PT. Tri Agung Abadi Medan. Research methods which used are descriptive statistic analysis coefficient correlation and coefficient of determinant, simple linear regression analysis and Z testing, The result of this research is there is influence of transformational leadership style toward job satisfaction at PT Tri Agung Abadi Medan. It can be proven from Z test that Z count (4.93) > Z table (1.96). The coefficient correlation value in 0.8889 that mean there is strong positive relationship between transformational leadership style with job satisfaction in PT Tri Agung Abadi Medan. The coefficient determination value in 79.00% that mean 79.00% of job satisfaction in PT Tri Agung Abadi Medan can be explained by transformational leadership style variable.